Apolipoprotein E Genotype Linked to Spatial Gait Characteristics: Predictors of Cognitive Dual Task Gait Change. - Rebecca K MacAulay; Ted Allaire; Robert Brouillette; Heather Foil; Annadora J Bruce-Keller; Jeffrey N Keller (PLoS ONE, 2016)
Developing measures to detect preclinical Alzheimer's Disease is vital, as prodromal stage interventions may prove more efficacious in altering the disease's trajectory. Gait changes may serve as a useful clinical heuristic that precedes cognitive decline. This study provides the first systematic investigation of gait characteristics relationship with relevant demographic, physical, genetic (Apolipoprotein E genotype), and health risk factors in non-demented older adults during a cognitive-load dual task walking condition.The GAITRite system provided objective measurement of gait characteristics in APOE-e4 "carriers" (n = 75) and "non-carriers" (n = 224). Analyses examined stride length and step time gait characteristics during simple and dual-task (spelling five-letter words backwards) conditions in relation to demographic, physical, genetic, and health risk factors.Slower step time and shorter stride length associated with older age, greater health risk, and worse physical performance (ps < .05). Men and women differed in height, gait characteristics, health risk factors and global cognition (ps < .05). APOE-e4 associated with a higher likelihood of hypercholesterolemia and overall illness index scores (ps < .05). No genotype-sex interactions on gait were found. APOE-e4 was linked to shorter stride length and greater dual-task related disturbances in stride length.Stride length has been linked to heightened fall risk, attention decrements and structural brain changes in older adults. Our results indicate that stride length is a useful behavioral marker of cognitive change that is associated with genetic risk for AD. Sex disparities in motor decline may be a function of health risk factors.